Methodology to prioritize pavements maintenance at network level - Thenoux, Guillermo; Halles, Felipe (Revista Ingeniería de Construcción, 2002)
One of the most important tasks which public and private agencies must undertake to either preserve or improve the level of service of the existing road network is that of determining the set of projects to be included in the preservation program for the period. In Chile as in most countries, resource allocation for the period is strongly influenced by two aspects: constraints affecting resources that can be allocated and the large number of variables requires for managing the process of evaluating and selecting pavements at network level. Selecting and prioritizing projects at network level requires for a structural and functional evaluation of pavements. Besides, it is necessary to include operating costs during a period under analysis that reflects the life cycle of the pavements. During the investigation, a simplified methodology to select and prioritize those projects having a greater need for maintenance were selected, mathematical formulas to calculate priority were developed, for both asphalt as well as PCC pavements. The priority formulas were developed modeling a group of pavements with different structural and serviceability conditions, evaluating the benefits that users derive from using a road in good serviceability condition. The priority formulas presented a correlation higher than 95%. The scope of the methodology to prioritize is such that it may be used by any agency responsible for a pavement network, without the need of sophisticated computer software.